Anak dan Pendidikan Anak Usia Dini dalam Cakrawala Al-Qur’an-Hadis - Warni Djuwita (Universitas Islam Negeri Mataram, 2011)
The study on children and early child education and its probelms from different perspectives has attracted researchers and academia. This paper focuses on studies of tarbiyah process and the developmental needs on golden age phase. The study is carried out employing the perspective of al-Qur’an and hadîts integrated with other knowledge of Psychology, Neuroscience, Medical Studies, and Sociology. From the integrated perspective, there becomes a universal principle that golden age phase is the most important stage in human life. This only comes once in the stage of human life cycle. If it passes without effective stimulation, this next stage of development potential is degrading. Children bearing such shortage are called “those who lost their childhood”.